2000
DOI: 10.1177/0093854800027003001
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Juvenile Criminal Recidivism

Abstract: This study focused on the outcomes of juvenile delinquents ( N = 140) following their conviction, commitment for residential placement, and return to the community on parole. Participants were followed for a period of 1 year postrelease. A random stratified sampling procedure was used to select participants from urban, suburban, and rural sites. Ratings of poor parole adjustment (73%), as well as observed rates of parole violation (73%) and reoffending (40%) across the entire sample reflected a substantial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Decades of research have found a huge number of factors significant to the origins and maintenance of delinquent behaviour (Skilling & Sorge, 2014), such as antisocial peers or attitudes, personality or misconduct problems, poor parent-child relations, educational difficulties and/or ineffective use of leisure time are the best predictors of delinquency (Campbell, Schmidt, & Wershler, 2016;Cauffman & Steinberg, 2012;Contreras, Molina, & Cano, 2011;Grieger & Hosser, 2014;Heilbrun et al, 2000;Simourd & Andrews, 1994). The domain of behavioural history is the strongest predictor of future delinquency (Casey, 2011;Cottle, Lee, & Heilbrun, 2001;Farrington, 2005;Frick, 2012;Frick, Ray, Thornton, & Kahn, 2014;Wasserman et al, 2003) meaning that the earlier the onset of behaviour problems, the worse predictions of desistance from antisocial behaviour are in the future (Dishion & Patterson, 2006;Loeber & Farrington, 2000;Moffitt, 1993Moffitt, , 2006.…”
mentioning
confidence: 99%
“…Decades of research have found a huge number of factors significant to the origins and maintenance of delinquent behaviour (Skilling & Sorge, 2014), such as antisocial peers or attitudes, personality or misconduct problems, poor parent-child relations, educational difficulties and/or ineffective use of leisure time are the best predictors of delinquency (Campbell, Schmidt, & Wershler, 2016;Cauffman & Steinberg, 2012;Contreras, Molina, & Cano, 2011;Grieger & Hosser, 2014;Heilbrun et al, 2000;Simourd & Andrews, 1994). The domain of behavioural history is the strongest predictor of future delinquency (Casey, 2011;Cottle, Lee, & Heilbrun, 2001;Farrington, 2005;Frick, 2012;Frick, Ray, Thornton, & Kahn, 2014;Wasserman et al, 2003) meaning that the earlier the onset of behaviour problems, the worse predictions of desistance from antisocial behaviour are in the future (Dishion & Patterson, 2006;Loeber & Farrington, 2000;Moffitt, 1993Moffitt, , 2006.…”
mentioning
confidence: 99%
“…Research has found, for example, that factors such as poor school performance, mental illness, substance abuse, learning disabilities, and family dysfunction (including child maltreatment) are all salient predictors of transition failure, defined primarily as recidivism (Bullis et al, 2002; Dembo et al, 1991; Heilbrun et al, 2000; Ryan & Testa, 2004). Other demographic factors such as being younger and male also predict less positive outcomes (Niarous & Routh, 1992; Heilbrun et al, 2000). …”
Section: Youth Reentry: Individual Barriers To Successmentioning
confidence: 99%
“…This focus is perhaps based on the assumption that individuals return to the same communities where they were arrested. Alternatively, prior research may have anticipated the influence of postrelease community context to be grounded in objective community characteristics (e.g., concentrated disadvantage, crime rate, jurisdictional supervision differences; Heilbrun et al, 2000; Huebner & Pleggenkuhle, 2015) rather than individuals’ subjective experiences of returning to a familiar or unfamiliar neighborhood. Although several studies have investigated outcomes related to individuals’ movements between communities or residences following release from incarceration (i.e., residential instability; Clark, 2016; Jacobs & Gottlieb, 2020), the possibility—and significance—of individuals’ changing communities from pre-incarceration to postrelease has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%